Neglected Inequality: Legal-Political Dynamics of Honorary Teacher Salaries in Indonesia’s Periphery through a Rawlsian Justice Lens - Muhtasib, Achmad; Fatimah, Siti; Husman, Aldi (Universitas Sains dan Teknologi Komputer, 2025)
The disparity in the welfare of honorary teachers, especially in the underdeveloped, frontier, and outermost (3T) regions of Indonesia, has become a structural issue that reflects the state's failure to provide social justice in education. Although honorary teachers have made significant contributions to supporting the national education system, their status remains marginal, lacking legal certainty, social security, and decent income. This research aims to examine the dynamics of injustice experienced by honorary teachers in 3T regions through the lens of social justice theory, as well as to explain how legal and educational policy contributes to the reproduction of these inequalities. The method employed is a qualitative approach with a critical case study design, involving in-depth interviews with honorary teachers and policymakers, as well as an analysis of regulatory documents. The research results show that injustice not only stems from low salaries but also from unequal access to professional training, disproportionate workloads, and systemic neglect of their voices in the decision-making process. Additionally, it was found that the presence of honorary teachers is often used as a cheap solution to fill teaching vacancies in 3T areas, without adequate structural reforms. This research makes a theoretical contribution by integrating the discourse of distributive and recognitive justice into educational policy and provides practical recommendations for the formulation of region-based affirmative policies. In conclusion, the disparity among honorary teachers is not merely a technical administrative issue, but rather a part of the crisis of social justice in national education that must be addressed through policy changes that are more equitable and contextually based.